Politically connected cities: Italy 1951-1991 - Guglielmo Barone; Guido De Blasio; Elena Gentili (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
The paper estimates the political connection premium for Italian cities tracked during the second half of the 1900s, when the role of the state in the economy was very widespread. It leverages the peculiar features of the gridlocked political landscape in place between the end of World War II and the fall of the Berlin wall, during which most influential politicians remained in charge for a very long time. We compare connected cities - small areas surrounding birthplaces of both prime ministers and leaders of the parties in power - with very similar, but unconnected municipalities, and find that politically connected cities gained a population premium of 8% over 40 years. When the connection ends, the difference in growth rate fades away. We document that birthplaces of powerful politicians benefited from both infrastructure investments and the location of plants by state-owned enterprises. Not surprisingly, the connection favored industrialization, raised employment and wages, but crowded out private entrepreneurship. Finally, our empirical evidence indicates that agglomeration economies in treated municipalities were not higher, thus suggesting that, if anything, place-based interventions linked to political connections have not been output-enhancing from a nationwide point of view.
Keywords: H50; R11; R12; 330; political connections; city growth